Zerologon flaw exploited in the wild. Issue 10 (October 2020) - Unknown
Abstract : The Zerologon vulnerability in Microsoft Server (CVE-2020-1472) is being increasingly targeted by both nation-state actors and cyber criminals due to a lack of patching.